An analysis of the shop houses facade and the special area plan of Taiping heritage town / Anne Foo Mei Mei and Helena Aman Hashim. - Foo Mei Mei, Anne; Hashim, Helena Aman (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2018)
Heritage towns in many countries are facing the pressure of redevelopment due to economic needs and also in the name of tourism. It is unfortunate that many a times, the conservation process is separated from development planning cum redevelopment thus destroying the urban fabric. Taiping is one such town that has been identified to be developed for heritage tourism under the Special Area Plan development plan upon its declaration as a Heritage Town in 1999. The Taiping Special Area Plan (TSAP 2010) was launched in 2010 with seven development plans set within the Taiping Town and the Lake Gardens Conservation Zone. The objective of this study is to explore the level and type of change to the façade characteristics of buildings located within Taiping Town Conservation Zone (TTCZ) since the implementation of TSAP 2010 and the conformance of these buildings with change to the TSAP 2010 guidelines. The research adopted a case study strategy with a field survey of the entire building units located within TTCZ followed by a document review of the TSAP 2010 guideline. The TTCZ photo inventory was cross-analysed with archival data to firstly identify the level of change based on a numerical rating scale. The data for building units with change were then analysed further to identify the type of change followed by its adherence to the TSAP 2010 guidelines. The findings revealed that there were changes to the building’s façade characteristics even though the overall magnitude of change was low. The changes were found to be mainly on the shop house typology as opposed to other typologies and the shop houses with changes did not adhere to the TSAP 2010 guidelines. The study concluded that the façade characteristics of building units has changed prior to 2010 and the TSAP 2010 guidelines may have not been implemented fully though this may need to be studied further.